Do Lending Relationships Matter? Evidence from Bank Survey Data in Germany - Erik Lehmann; Doris Neuberger (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
Strong lending relationships between banks and small and medium-sized enterprises (SMEs) play a key role in the bank-based financial system of Germany. So far, they have been mainly described by the notion of a housebank and transactional features of long-term bank-customer relationships. In contrast, the present paper also considers interactional variables which try to measure social relations between loan officer and firm manager. Using bank survey data, the relationship and interaction variables prove to affect loan prices, collateral requirements and credit availability.
urn:nbn:de:bsz:352-opus-4193
Keywords: 330; Kredit; Firmenkundengeschäft; Bank; KMU; Lieferanten-Kunden-Beziehung; Social Capital; Schätzung; Deutschland